Trade openness and economic growth in Turkey: A rolling frequency domain analysis - Emrah İ. Çevik; Erdal Atukeren; Turhan Korkmaz (Economies, 2019)
Taking Turkey's experience as a case study, this study provides further insights into the evaluation of time-varying Granger-causal relationships in the trade openness and economic performance nexus. We reinvestigated the Granger-causal relationships between trade openness and real economic growth in Turkey for the time period 1950-2014. We employed a rolling version of Breitung and Candelon's frequency domain Granger-causality test, which allowed us to identify the changes in the nature of the causal relationships overtime. Hence, in the face of different results found in the literature overtime, our study provides a more unified evidence on the relationship between trade openness and real economic growth in Turkey. In addition, we found empirical evidence for the possibility of a distinct temporal ordering in a feedback relationship between trade openness and economic growth. We called this situation "sequential feedback".
Keywords: C32; F14; F43; O47; 330; openness and economic growth; Granger-causality; frequency domain time series analysis; Turkey